Strategi Keberlanjutan Dalam Mempertahankan Lahan Pertanian Pangan Di Kabupaten Bogor - Judo Satria; A Faroby Falatehan; Irfan Syauqi Beik (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2024)
This research is conducted based on the challenges faced by the agricultural sector in Bogor Regency, namely the conversion of rice fields. This conversion occurs due to population growth and economic development in the Bogor Regency, which serves as a buffer zone for the Special Capital Region of Jakarta. The aim of this research is to formulate alternative strategies as efforts for sustainable protection of agricultural land in Bogor Regency using the Analytical Hierarchy Process (AHP) method. Based on the results of the AHP vertical analysis, at the priority factor level is Community Empowerment. At the stakeholder level, private sector prioritizes Community Empowerment. The constraint level prioritizes Lack of Collaboration with Local Government. At the alternative strategy level, the priority is the Establishment of a Sustainable Agricultural Land Control Team with academic support. Keywords: Agricultural Land Conversion, Analytic Network Process, Food Agricultural Land, Strategy